Melanogenesis inhibition by palm tocotrienol rich fraction in cellular ageing - Suzana M,; Nur Nadia MA,; Zahariah I,; Chua KH,; Yasmin Anum MY,; Wan Zurinah WN, (Penerbit UKM, 2009)
Melanin is the pigment that determines skin color. Melanin synthesis is catalysed by the enzyme tyrosinase and is controlled by TYR, TYRP1 and TYRP2 genes. In this study, tocotrienol rich fraction (TRF) was used to inhibit melanin synthesis. TRF contains 75% α-tocotrienol and 25% tocopherol. The objective of this study was to determine the effect of tocotrienol rich fraction (TRF) on melanin synthesis by determining melanin content and expression of genes involved in the regulation of melanin synthesis in skin melanocytes. Melanin synthesis was studied by determining melanin level and tyrosinase enzyme activity, while expression of TYR, TYRP1 and TYRP2 genes was determined by quantitative real time reverse transcriptase poly-merase chain reaction (real time RT-PCR). Primary culture of skin melanocytes were divided into two groups; control and cells that were treated with 500 μg/ml tocotrienol rich fraction for 24 hours. Our results showed that there was a reduction in melanin content and tyrosinase activity in skin melanocytes treated with tocotrienol rich fraction compared to the control (p<0.05). Expression of TYRP2 gene in melanocytes treated with tocotrienol rich fraction was also decreased (p<0.05) compared to the control. In conclusion, palm tocotrienol rich fraction has anti pigmentation property that inhibits melanin synthesis in cellular aging by inhibiting tyrosinase activity and down regulating TYRP2 gene expression.